The Moderating Role of Interpersonal Mindfulness in the Relationship Between Social Media Use and Marital Satisfaction - Riahifar, Maryam; Abdollahi, Abbas; Vakili, Samira (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present study aimed to investigate the moderating role of interpersonal mindfulness in the relationship between social media use and marital satisfaction. Methods: This study was descriptive and correlational in terms of its objectives and the manner of data collection. The sample population consisted of married individuals who used social media and resided in Tehran, from whom 160 people were selected using a convenience sampling method. In this research, the Interpersonal Mindfulness Scale by Steven Puchter et al. (2018), the Social Networks Scale by Mojdeh et al. (2014), and the Marital Satisfaction Scale by Enrich were used. To evaluate the structural model of the study, the four-stage structural assessment model proposed by Hair et al. (2017) was utilized. Findings: The results indicated a significant positive correlation between interpersonal mindfulness and marital satisfaction, and a significant negative correlation between the extent of social media use and marital satisfaction (P = 0.05). Conclusion: Ultimately, the findings demonstrated that the moderating role of interpersonal mindfulness in the relationship between social media use and marital satisfaction is significant.